2002
DOI: 10.1016/s0893-133x(02)00378-0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-hydroxybutyrate Reduces GABAA-mediated Inhibitory Postsynaptic Potentials in the CA1 Region of Hippocampus

Abstract: Gamma-hydroxybutyric acid (GHB) is a psychoactive drug and a putative neurotransmitter, derived from gammaaminobutyric acid (GABA). At micromolar concentrations GHB binds to specific high and low affinity binding sites present in discrete areas of the brain, while at millimolar concentrations GHB also binds to GABA B receptors. Previous studies indicated that GHB inhibits bothGamma-hydroxybutyric acid (GHB) is a psychoactive drug and a putative neurotransmitter (Bernasconi et al. 1999;Maitre 1997). Administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
(59 reference statements)
2
18
0
1
Order By: Relevance
“…Moreover, the dose-response relationship (Figure 1g) and previous reports showed maximal and specific action of GHB at the concentration of 600 mM (Berton et al, 1999;Cammalleri et al, 2002). It should be noted that previous studies (Madden and Johnson, 1998;Erhardt et al, 1998;Shepard and Connelly, 1999) reported an inhibitory effect of GHB on nigral dopamine neurons.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, the dose-response relationship (Figure 1g) and previous reports showed maximal and specific action of GHB at the concentration of 600 mM (Berton et al, 1999;Cammalleri et al, 2002). It should be noted that previous studies (Madden and Johnson, 1998;Erhardt et al, 1998;Shepard and Connelly, 1999) reported an inhibitory effect of GHB on nigral dopamine neurons.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, it has been previously shown that GHB receptors are found mostly on nerve terminals (Maitre et al, 1983). A presynaptic mechanism of action of GHB has also been proposed in the hippocampus in experiments on paired pulse facilitation (Berton et al, 1999) or following exogenous application of GABA (Cammalleri et al, 2002). A presynaptic mechanism underlying the effect of GHB does not conflict with the observed reduction of sIPSCs amplitude.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The majority of GABA A receptors contain a ␥2 subunit, expressed throughout the brain except in the thalamus. It is well known that GHB administration in rats modifies GABA release in brain (9,10,28), leading to a pharmacological profile (sleep, anesthesia, anxiolysis) similar to those described for other GABA A agonists.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the ␥2 chain of GABA A receptor was downregulated by the drug. This could be due to a sustained hyperstimulation because GABA A receptors seem to play a pivotal role in the functional and pharmacological effects of GHB (1,5,10,16,23,63). The majority of GABA A receptors contain a ␥2 subunit, expressed throughout the brain except in the thalamus.…”
Section: Discussionmentioning
confidence: 99%